Microplastic pollution in the surface waters of Italian Subalpine Lakes. (May 2018) - Sighicelli, Maria; Pietrelli, Loris; Lecce, Francesca; Iannilli, Valentina; Falconieri, Mauro; Coscia, Lucia; Di Vito, Stefania; Nuglio, Simone; Zampetti, Giorgio
Abstract: Plastic debris incidence in marine environment was already highlighted in the early 1970s. Over the last decade, microplastic pollution in the environment has received increasing attention and is now an emerging research area. Many studies have focused on quantifying microplastic abundance in the marine environment, while there are relatively few data on microplastic occurrence in freshwater environment. Recent studies have reported high concentrations of microplastics in lakes and rivers, although the understanding of several factors influencing source, transport and fate is still limited. This study compares different lakes and the common factors, which could influence the occurrence and distribution of microplastics. The three subalpine lakes monitored include Lake Maggiore, Iseo and Garda. The selected sampling transects reflect the hydrologic conditions, the morphometric characteristics of these lakes, and other factors influencing the release of plastics debris in lakes. Particles of microplastics (<5 mm) were found in all sampled surfaces. The particles collected were classified depending on their number, shape and composition. The shape distribution showed the dominating occurrence of fragments (73.7%). The chemical composition of all examined samples clearly shows dominating presence of polyethylene (45%), polystyrene (18%) and polypropylene (15%). The results provide significant relations among the different contribution of direct and diffuse sources to the quantity of microplastics, highlighting the importance of understanding the spatial distribution dynamics of microplastics within a lake system that acts as a sink and source of plastic particles. Graphical abstract: Image 1 Highlights: Presence of microplastics (MP) in Italian freshwater systems. Shape distribution and plastic composition comparable to marine environment. Spatial distribution dynamics of MP related to direct and diffuse sources. Need to understand role of the main tributaries as input and output of MP. Abstract : The significant presence of microplastics in Italian freshwater systems and the spatial variation in microplastic concentration confirm the importance of the input sources.